Subgrouping‐based multicast transmission over high‐throughput satellite systems with beam cooperation. (27th April 2020) - Zhang, Shuo; Yang, Mingchuan; Wei, Yuming; Guo, Qing
Summary: This paper investigates the multicast transmission for multicast services in high‐throughput satellite (HTS) systems. Considering the multibeam multicast feature of HTSs, cooperative transmission among beams is involved in to improve the efficiency of the multicast transmission. Since the multicast transmission rate depends on the worst user channel state, all the users experience an unreasonably low rate. In this situation, subgrouping techniques are employed to increase transmission rates of users. A subgrouping‐based multicast transmission problem aiming at maximizing the lowest transmission rate of the users is studied to guarantee fairness among users. We formulate the problem as a max–min optimization problem and propose two low‐complex subgrouping algorithms for this problem. Additionally, we also consider multicasting in a single beam and devise a two‐layer transmission scheme for it. In the performance evaluation part, besides the impact of parameters on subgrouping performance, we analyze the performance and the computational complexity of the proposed algorithms. The results indicate that the two subgrouping algorithms can achieve favorable performance with low complexity. Abstract : This paper performs an investigation of the multicast transmission for multicast services in High Throughput Satellite (HTS) systems. The cooperative multicast transmission of the beams is considered to fully utilize the co‐frequency interference to promote the transmission. Further, subgrouping technique is employed to increase the transmission efficiency and two low‐complex subgrouping algorithms are proposed.Figure 1 in the article can be used as the eye catching figure.The short abstract is as follows: This paper performs an investigation of the multicast transmission for multicast services in High Throughput Satellite (HTS) systems. The cooperative multicast transmission of the beams is considered to fully utilize the co‐frequency interference to promote the transmission. Further, subgrouping technique is employed to increase the transmission efficiency and two low‐complex subgrouping algorithms are proposed.